2019
DOI: 10.1111/hae.13695
|View full text |Cite
|
Sign up to set email alerts
|

Safety of buccal infiltration local anaesthesia for dental procedures

Abstract: Aim To assess the safety of buccal infiltration local anaesthetic (LA) without additional factor replacement in patients with haemophilia (PWH) and association with clinical experience of the operator. Methods A consecutive sample of participants with mild, moderate and severe haemophilia scheduled to have dental treatment were recruited from a comprehensive care centre in Ireland. Infiltration LA was administered using a standard technique. Safety was defined as any adverse event at time of administration, im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 15 publications
0
19
0
1
Order By: Relevance
“…Only two minor hematomas were found in the study group, and no prolonged hemorrhage was observed. Dougall et al [ 74 ] determined the safety of buccal infiltration anesthesia in patients with hemophilia based on the severity of hemophilia (mild, moderate, or severe). The clinical experience of practitioners was categorized as less or more than 3 years of experience.…”
Section: Resultsmentioning
confidence: 99%
“…Only two minor hematomas were found in the study group, and no prolonged hemorrhage was observed. Dougall et al [ 74 ] determined the safety of buccal infiltration anesthesia in patients with hemophilia based on the severity of hemophilia (mild, moderate, or severe). The clinical experience of practitioners was categorized as less or more than 3 years of experience.…”
Section: Resultsmentioning
confidence: 99%
“…Local anesthesia often becomes an indispensable element of the dental procedure. It is assumed that infiltration anesthesia administered from the vestibule side of the mouth is safe for patients with hemophilia, and the earlier administration of a deficient coagulation factor has no effect on potential complications [ 61 ]. Safe anesthesia in this group of patients also includes pulpal anesthesia, periodontal anesthesia and mental nerve block.…”
Section: Resultsmentioning
confidence: 99%
“…Safe local anesthesia [ 59 , 60 , 61 ] infiltration anesthesia from the side of the oral vestibule pulpal anesthesia periodontal anesthesia mental nerve block …”
Section: Tablementioning
confidence: 99%
“…For instance, in this case, the dentist decide to use buccal infiltration LA, as it is more comfortable and safer than block injection 17 . A cross‐sectional observational study reported a high success rate (99%) with no adverse bleeding of buccal infiltration LA in 95 patients with haemophilia 18 …”
Section: Discussionmentioning
confidence: 99%